2019
DOI: 10.1016/j.scienta.2019.108778
|View full text |Cite
|
Sign up to set email alerts
|

Potential of wall rocket (Diplotaxis erucoides) as a new crop: Influence of the growing conditions on the visual quality of the final product

Abstract: Highlights Wall rocket leaf morphology is different from other rocket crops. Morphological differentiation can be used to enhance and promote it as new crop. Significant inter-and intra-population variation was detected among accessions. High environmental effects resulted in low heritabilities. Field cultivation promotes lobated, dark green leaves, commercially appreciated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 32 publications
(40 reference statements)
2
10
1
Order By: Relevance
“…Thus, the traits analyzed in the present work were not useful enough to clearly separate among them. These results are in contrast to our previous work evaluating the leaf morphology in the three species, where materials were clearly differentiated by the shape and size of leaves [29]. In consequence, the exploitation of distinctiveness in wall rocket with a commercial purpose could focus on other traits such as visual traits.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Thus, the traits analyzed in the present work were not useful enough to clearly separate among them. These results are in contrast to our previous work evaluating the leaf morphology in the three species, where materials were clearly differentiated by the shape and size of leaves [29]. In consequence, the exploitation of distinctiveness in wall rocket with a commercial purpose could focus on other traits such as visual traits.…”
Section: Discussioncontrasting
confidence: 99%
“…In a second analysis, the 11 accessions of wall rocket were compared among systems under two different growing periods. It has been previously observed that the growing period in a short-cycle species such as wall rocket can affect its morphology [29,47]. Moreover, the accumulation of different compounds such as nitrates can be affected by the growing period as well, as Bonasia et al [48] described for wild rocket.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations